The relationships between impulsivity and mood in bipolar disorder: an ecological momentary assessment study - Ramírez-Martín, Almudena; Sirignano, Lea; Foo, Jerome Clifford; Streit, Fabian; Frank, Josef; Witt, Stephanie; Rietschel, Marcella; Mayoral-Cleries, Fermin; Moreno-Küstner, Berta; Guzmán-Parra, Jose (PLOS ONE, 2025)
Background Impulsivity is a key feature of bipolar disorder (BD) associated with various negative outcomes. Recent use of ecological momentary assessment (EMA) has allowed for nuanced examination of the mechanisms of mood and impulsivity dysregulation. However, few existing studies have used an ecological momentary assessment of impulsivity in multiplex families with BD and examined its associations with mood. Objective Using EMA, this study investigated the concurrent and predictive relationships between impulsivity and mood. Methods Multiplex family members with BD (BDF, n = 8), unaffected family members (FC, n = 6), individuals with BD not from families (BDC, n = 8) and healthy controls (HC, n = 8), completed daily EMA surveys about mood and impulsivity for 6-12 weeks. Mixed-effects regression concurrent and lagged models were employed to analyze the relationship between impulsivity and mood. Results The BDF (Diff = −31.70, p = 0.001) and BDC (Diff = −25.74, p = 0.007) groups had a significantly lower mean in mood scores compared to the HC group but not compared to the FC group. There were no significant differences in the mean impulsivity scores between the groups. Time-lagged analyses revealed a significant negative association between prior impulsivity and mood at the next assessment independent of diagnosis (OR=0.939, p = 0.002). However, the opposite relationship between prior mood and impulsivity was not significant (OR=0.996, p = 0.135). Conclusions These results contribute to the understanding of the complex interactions between BD, the genetic load of the disorder, impulsivity and mood. Furthermore, these findings indicate the potential benefits of addressing impulsivity as a means to improve mood outcomes at an early stage.
Gesehen am 12.08.2025